2019
DOI: 10.18267/j.cebr.216
|View full text |Cite
|
Sign up to set email alerts
|

Online Grocery Shopping Acceptance: The Impact on the Perception of New Technologies and Loyalty in Retailing

Abstract: Online grocery shopping is becoming an integral part of life for more and more customers around the world and has truly changed the way consumers acquire their groceries. Nevertheless, the offline environment is still a priority for most customers. Therefore, it is not surprising that new technologies are also being introduced in traditional stores. The purpose of this paper is to explore if all generations of customers equally perceive pressure to apply new technologies into the purchasing process and how pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…35 The studies covered a range of issues related to online retail of foods, from retailer perspectives [36][37][38][39] to consumer attitudes toward buying groceries online. 32,[40][41][42][43][44][45] Online food delivery services (of fast food and other ready meals) [46][47][48] also emerged as part of the typology of food vendors in the digital food environment. This includes restaurants and other vendors of ready meals that have their own smartphone applications and websites, as well as third party food delivery aggregators (such as Swiggy, Zomato, and Uber Eats).…”
Section: External Domainmentioning
confidence: 99%
“…35 The studies covered a range of issues related to online retail of foods, from retailer perspectives [36][37][38][39] to consumer attitudes toward buying groceries online. 32,[40][41][42][43][44][45] Online food delivery services (of fast food and other ready meals) [46][47][48] also emerged as part of the typology of food vendors in the digital food environment. This includes restaurants and other vendors of ready meals that have their own smartphone applications and websites, as well as third party food delivery aggregators (such as Swiggy, Zomato, and Uber Eats).…”
Section: External Domainmentioning
confidence: 99%
“…A Scopus search of the latest research trends on the factors shaping patronage of bricks-and-mortar grocery retailing under the context of widespread online shopping revealed that several empirical studies had been published in leading journals (See Appendix for details of the systematic review we conducted). Of the eight studies discussing the impact of the diffusion of digital technologies on grocery retail brick-and-mortar patronage, three studies discuss how using mobile apps affects brick-and-mortar shopping behaviour and retail patronage (Bies et al, 2021;Lim et al, 2022;Klabjan and Pei, 2011), two studies discuss how the introduction of online shopping affects retail patronage in online and offline shopping (Bauerov a, 2019;Melis et al, 2016); two studies examine the impact of in-store digital signage on retail patronage (Garaus et al, 2017;Garaus and Wagner, 2019) and one study discusses the formation of retail patronage in a click-and-collect (Vyt et al, 2022). Whilst existing studies have initiated new horizons in the retail literature, online grocery shopping has only been around for a short time, leaving many areas unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Millennial Y values these ratings and relies on them as a personal reference when purchasing products and services. E-commerce services are popular among the Millennial Y generation because they provide high-quality services, promotions, discounts, and free shipping, (Amin and Rahman (2015); San, et al, (2015); Petra (2016); Cavagnaro, et., (2018); Shafiq, et al, (2019); Ishak, et al, (2019); Simanjuntak (2019); Bauerova (2019); Porral and Menggoti (2019) ;Ismail, et al, (2020).…”
Section: Introductionmentioning
confidence: 99%